The optimal biliary reconstruction for pancreaticobiliary maljunction and congenital biliary dilatation: Clinical comparison between hepaticojejunostomy and hepaticoduodenostomy (Journal of Paediatric Surgeons of Bangladesh, 2018)
Background: The most important factors determining the optimal biliary reconstruction procedure for pancreaticobiliary maljunction (PBM) and congenital biliary dilatation (CBD) include remote malignant potential and postoperative complications. The aim of this study is to clarify which is more optimal, hepaticojejunostomy (HJ) or hepaticoduodenostomy (HD). Methods: Seventy-seven pediatric patients with PMD and CBD, treated in our institution between 1985 and 2009, were reviewed in terms of clinical outcomes and postoperative complications. Forty-three underwent HJ and 34 HD, 6 of whom underwent laparoscopy-assisted surgery.Results: Anastomotic stenosis developed in one case of each group, which was treated with percutaneous transhepatic balloon dilation in a case of HJ and endoscopic balloon dilation in a case of HD. Intestinal obstruction related with a Roux-en-Y loop in 4 cases of HJ, 3 of which necessitated laparotomy. Postoperative endoscopy was performed in 14 cases of HD, and demonstrated gastritis in one case of them. No malignancy or cholangitis developed in both groups during the follow-up period.Conclusions: The possible indirect cause of biliary malignancy, intrahepatic bile-duct stenosis or cholangitis, was not encountered in either procedure, whereas postoperative intestinal obstruction was only in HJ. HD can be more optimal as a biliary reconstruction procedure for PBM and CBD.Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 50-54